THE USAGE OF PHYSIOTENSE IN ELDERLY PATIENTS WITH ESSENTIAL HYPERTENSION - O. D. Ostroumova; V. I. Mamayev; M. V. Nesterova; Y. A. Bagramova; T. E. Rybkina; S. Y. Gedgafova; I. A. Kuzmichev (Российский кардиологический журнал)
The usage of physiotense in elderly patients with essential hypertension.